2003
DOI: 10.4161/cbt.2.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Suppression of the TRAIL Death-Receptor Pathway in Chemotherapy Sensitive and Resistant Follicular Lymphoma Cells

Abstract: Aberrant expression of the apoptosis inhibitor bcl-2 provides a survival advantage throughout oncogenesis and can facilitate chemotherapeutic resistance in a variety of human cancers. Follicular lymphoma (FL) for example, is characterized by the chromosomal translocation t(14;18), which results in bcl-2 overexpression and initiates lymphomagenesis. Although FL cells possess ample amounts of bcl-2, they respond remarkably well to standard first-round chemotherapy. However, the vast majority of patients relapses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…These antibodies bind and activate DR5 but not other tumor necrosis factor receptors including DR4 and the TRAIL decoy receptors DcR1 and DcR2 (20). Consistent with our previous studies using recombinant TRAIL, siCaspase-2 also suppressed DR5-A-mediated reduction in cell viability (Fig.…”
Section: Silencing Caspase-2 Expression With Small Interfering Rnassupporting
confidence: 91%
“…These antibodies bind and activate DR5 but not other tumor necrosis factor receptors including DR4 and the TRAIL decoy receptors DcR1 and DcR2 (20). Consistent with our previous studies using recombinant TRAIL, siCaspase-2 also suppressed DR5-A-mediated reduction in cell viability (Fig.…”
Section: Silencing Caspase-2 Expression With Small Interfering Rnassupporting
confidence: 91%
“…53 In human tumors, Cillessen et al 54 observed that TRAIL receptor-2 levels are lower in TRAIL-resistant DLBCL, but no data on TP53 were provided in their study. Wagner et al 55 have previously shown, in a microarray analysis of chemoresistant follicular lymphoma cell lines with TP53 mutations, that the abnormal p53 protein cannot up-regulate TRAIL receptor-2 after cells encountered stress from either etoposide or doxorubicin treatment in vitro, which does occur in cell lines with WT TP53. Similarly, Rosenwald et al 28 showed that the level of TRAIL receptor-2 is not up-regulated in a lymphoblastoid cell line with a TP53 mutation treated with fludarabine or irradiation, or in a fludarabine-resistant chronic lymphocytic leukemia with p53 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that the use of exogenous TRAIL or antibodies to TRAIL receptor-2 will stimulate the receptor with the regain of normal apoptosis in lymphoma cell lines with TP53 mutations, [54][55][56] including cell lines derived from DL-BCL. 54 This is in contrast to chronic lymphocyte leukemia or mantle cell lymphoma in which TRAIL receptor 1 (DR4) is activated, but TRAIL receptor-2 is not up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented in the literature that activation of the TRAIL apoptotic pathway such as up-regulation of DR5 contributes to the induction of apoptosis by certain anticancer agents, including celecoxib (Huang et al, 2001;LaVallee et al, 2003;Wagner et al, 2003;Liu et al, 2004b;Kabore et al, 2006). The current work does not address whether DR5 up-regulation participated in the induction of apoptosis by DMC only, although we assume that it may contribute to DMC-induced apoptosis because celecoxib induces apoptosis requiring DR5 up-regulation.…”
Section: Sensitization Of Trail-induced Apoptosis By Dimethyl-celecoxmentioning
confidence: 99%